Understanding employees' responses to the COVID‐19 pandemic: The attractiveness of healthcare jobs. Issue 2 (26th November 2020) - AL‐Abrrow, Hadi; Al‐Maatoq, Marwa; Alharbi, Raed Khamis; Alnoor, Alhamzah; Abdullah, Hasan Oudah; Abbas, Sammar; Khattak, Zeeshan Zaib
Abstract : The purpose of this study was to examine the impact of COVID‐19 on the attractiveness of work in the Iraqi health sector by looking at the mediating role of employees' attitudes. A questionnaire survey was used to collect data from 218 health sector employees. The results revealed that there is a significant impact of COVID‐19 pandemic on employees' attitudes that influence their decision to quit the health sector and look for jobs in other sectors. As health sector employees are prone to suffer the most in the pandemic, this crisis significantly affected the attractiveness of jobs in the health sector, leading to an increase in employees' negative attitudes and their desire to leave work.